Tradução intersemiótica: nos rastros do filme Apocalypse Now - Faria, Alisson Costa de (2014)
The actual research analyzes the translational relations from the movie Apocalypse Now (1979), from Francis Ford Coppola, with its sources, especially the novel The Heart of Darkness (2006), from Joseph Conrad and Dispatches (2005), from Michael Herr. The objective was to investigate how the cinematographic masterpiece was built from the intersemiotic translations of its sources. This research also analyzes the meanings developed by the masterpiece, pointing to convergent and dissonant points with its sources, verifying how the elements transposition (time, space, points of views, conflicts and characters) of literary and journalistic texts for the movie happen to be. The research justifies in the fact that the movie of Coppola does not translate in a sequence the novel narrative of Conrad and the other texts used for the movie industry, but to change concepts and ideas into moving images. Convencionally, this kind of criticism sees the adaptation tasks by certain kind of criteria like accuracy of the movie text in relation to the literary text. It needs to be understood how the translation process happens between sources and adaptation, respecting the specificities of each semiotic system, making the intersemiotic translation a method that can create a new masterpiece and not just a identity copy, from one to another. The movie Apocalypse Now creation process is also the object of this research and will be guided by the Genetics Criticism elements. Interpretations from authors who are considered references on the theme were considered, such as: Robert Stam, Julio Plaza, Sergei Eisenstein, Cecília Salles. In terms of method, scenes, parts and frames from Apocalypse Now were analyzed, starting by the surface thoughts, as Flusser teaches us, opposing to line thoughts, that can be found in literary texts. The movie production entry were also analyzed, like the documentary Hearts of Darkness: A Filmmaker's Apocalypse (1991), with its coulisse, both realyzed by Eleanor Coppola, such as interviews with the diretor, screenwriter and the actors of the movie